1976
DOI: 10.1159/000180713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Middle-Sized Molecule Aggregates from Dialysate of Uremic Patients on Lymphocyte Transformation <i>in vitro</i>

Abstract: It was found that middle-sized molecules obtained from dialysate of uremic patients caused suppression of PHA-induced lymphocyte transformation. This was expressed by the lowering of labeled leucine incorporation and by the suppression of lymphocyte transformation as morphologically assessed. In view of the presented data middle-sized molecules seem to be biologically active substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…The inhibitory concentration in vitro is within the level measured in uremic serum [69]. These mole cules have been shown to suppress phyto hemagglutinin-induced lymphocyte transfor mation [68]. HD can reduce the level of mid dle molecules with improvement in lympho cyte function [30].…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…The inhibitory concentration in vitro is within the level measured in uremic serum [69]. These mole cules have been shown to suppress phyto hemagglutinin-induced lymphocyte transfor mation [68]. HD can reduce the level of mid dle molecules with improvement in lympho cyte function [30].…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 98%
“…54, 63], Several kinds of molecular substances are found in uremic serum (table IV). Substances referred to as middle molecules such as methyl guanidine, guanidinosuccinic acid are elevated [66,68]. Methyl guanidine decreases the mixed-lym phocyte reaction at 7.5 pg/ml and suppresses it completely at 60 pg/ml [67].…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 99%
“…We will only mention the principal effects attributed to MM, a detailed study of these effects being the subject of another publication [47]: inhibitory effect on the synthesis of globin in vitro [36] and in vivo [8] and on some enzymes responsible for the synthesis of heme [35]; inhibitory effect on E-rosette formation [1]; inhibition of phagocytosis [52,53]; inhibition of leukocyte migration [13]; inhibition of the glucose utilization in vitro [18]; inhibitory effect on the in vitro proliferation of lymphocytes in the presence of allogeneic cells [19,50,58,59], of mitogens [30,50,57], of fibroblasts [21,44,48] and of tumoral cells of human origin [48]; inhibitory effect on the graft-versus-host reaction in mice and rats [51]; inhibition of nervous conduction in vitro [42],…”
Section: Biological Role O F MMmentioning
confidence: 99%
“…Several authors have reported that the increased con centrations of the so-called 'middle molecules' (MMs) as postulated in the middle molecule hypothesis [7], which would normally be removed by the kidneys, may contribute significantly to the uremic syndrome [8][9][10][11][12][13][14][15][16][17]. It seems highly probable that MMs are peptidic substances [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many authors have reported the increased concentrations of peptides in uremic blood and some of which have toxicity [8][9][10][11][12][13][14][15][16][17], In addition, it is well known that the blood levels of many peptide hormones are elevated in patients with uremia [6], Recently, Massry and Goldstein [34] have stressed that parathyroid hormone is a major uremic toxin. Abiko et al [35][36][37] have isolated the tripeptide (His-Gly-Lys), the heptapeptide (His-Pro-Ala-Glu-AsnGly-Lys) and the pentapeptide (Asp-Leu-Trp-Gln-Lys) from the UF of blood obtained from uremic patients.…”
mentioning
confidence: 99%